Method for rapidly preparing lithium manganese iron phosphate positive electrode material

By using hydrophilic organic solvents and water mixing solvents to quickly stirring reaction to prepare manganese iron front -drive body, combined with wet ball grinding and two staircase burning, solving manganese lithium -lithium -lithium orthopedic material has uneven granularity, long preparation time, stable cycle cycle Poor sexual problems realize efficient and fast material preparation and excellent electrochemical properties.

CN119349530APending Publication Date: 2025-01-24DONGFENG MOTOR GRP

Patent Information

Application Number
CN202411181189.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing synthesis process of lithium manganese iron phosphate positive electrode materials has problems such as uneven particle size, long preparation time, and poor cycle stability, which limits its wide application in the field of electric vehicles.

Method used

Use hydrophilic organic solvents and water to form a hybrid solvent, dissolve oxalic acid, and quickly stir at room temperature to prepare manganese iron front -drive body, and then perform wet ball grinding and two staircase burns to make manganese phosphate iron lithium positive electrode materials Essence

Benefits of technology

It achieves rapid nucleation of the precursor and refinement of the particle size, shortens the preparation time, improves the cycle stability and electrochemical performance of the material, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349530A_ABST
    Figure CN119349530A_ABST
Patent Text Reader

Abstract

The invention discloses a method for rapidly preparing a lithium manganese iron phosphate positive electrode material, which comprises the following steps: S1, forming a mixed solvent by using a hydrophilic organic solvent and water according to a volume ratio of (1-8): 1, dissolving oxalic acid in the mixed solvent to obtain an organic / water blended oxalic acid solution, synchronously and rapidly pouring a bivalent manganese salt solution and a bivalent iron salt solution into the organic / water blended oxalic acid solution, and uniformly stirring to obtain a mixed solution; stirring and reacting at room temperature for 0.5-4 hours, separating, washing and drying to obtain precursor powder; s2, performing wet ball milling on the precursor powder, a lithium source, a phosphorus source and a carbon source, taking out and drying for later use; and S3, calcining the mixture, cooling after calcining, and grinding to obtain the lithium iron manganese phosphate positive electrode material. According to the method, the precursor time is greatly shortened, the energy consumption is reduced, the oxidation of metal ions in the preparation process is effectively avoided, the product purity is improved, and the preparation of the high-quality lithium iron manganese phosphate positive electrode material is realized by controlling the particle size of the precursor and the distribution of metal atoms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium batteries, and in particular to a method for rapidly preparing lithium manganese iron phosphate positive electrode materials. Background Art

[0002] In recent years, the sales of new energy vehicles have exploded, but the range anxiety problem has always existed. As the core component of new energy vehicles, the development of battery energy density has been close to its theoretical value. Therefore, it is urgent to develop a new generation of battery material system. Lithium manganese iron phosphate material (LiMn x Fe 1-x PO4) is a lithium iron phosphate (LiFePO4) doped with a certain proportion of manganese (Mn). It has a higher voltage platform (increased to 3.8-4.1V), an energy density 10%-20% higher than LiFePO4, and better low-temperature performance. It is considered to be an upgraded version of LiFePO4 material. However, the introduction of manganese will lead to lower electronic conductivity and ion mobility of the material, poor rate performance and cycle performance, etc., which restricts the widespread application of lithium manganese iron phosphate positive electrode materials in the field of electric vehicles.

[0003] At present, there are two main synthetic process routes for lithium iron manganese phosphate materials: solid phase method and liquid phase method. The solid phase method is the most traditional method, with relatively simple equipment and process, which is conducive to mass production, but the synthesis temperature is high, the time is long, it is difficult to control the particle size and distribution of the product, the uniformity is poor, and it is difficult to obtain ideal electrochemical performance. The most commonly used liquid phase manufacturing method is to first form an iron manganese phosphate intermediate, and then add a lithium source to obtain lithium iron manganese phosphate. In the preparation process of the iron manganese phosphate precursor, it is easy to be oxidized and accompanied by the generation of impurities, and the preparation process is relatively complicated, the synthesis cycle is long, the product is not easy to dry, industrialization is difficult, and the production cost is high.

[0004] CN 117334874 A discloses a lithium iron manganese phosphate positive electrode material that achieves atomic-level mixing of iron and manganese, and a preparation method and application thereof. The preparation method comprises: (1) preparing ammonium oxalate, a soluble iron source, and a soluble manganese source into aqueous solutions respectively, stirring the three solutions to react, filtering, washing, and drying the precipitated mixture to obtain a blocky iron manganese oxalate precursor with uniform particle size; (2) mixing the precursor, lithium source, phosphoric acid source, carbon source, and solvent for the first ball milling; (3) drying the first slurry and then performing the first roasting, mixing the roasting product, carbon source, and solvent for the second ball milling; (4) drying the second slurry and then performing the second roasting to finally obtain the lithium iron manganese phosphate positive electrode material. This scheme adopts a step-by-step method to prepare the lithium iron manganese phosphate positive electrode material to achieve atomic-level mixing of iron and manganese, but the size of the precursor is not controlled. From the SEM image, it can be seen that the particle size of the precursor is about 10 to 40 μm, and the battery performance finally displayed is poor. In addition, the reaction time of co-precipitation is 8-20 hours, which is not conducive to industrial production. Moreover, the two-step ball milling process is time-consuming and energy-consuming.

[0005] Therefore, it is urgent to develop a new lithium iron manganese phosphate precursor and lithium iron manganese phosphate positive electrode material synthesis process route, which can not only quickly prepare the lithium iron manganese phosphate precursor and greatly reduce the preparation time of the precursor, but also reduce the particle size of the precursor and improve the cycle stability of the lithium iron manganese phosphate positive electrode material. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the above-mentioned background technology and provide a new lithium iron manganese phosphate precursor and a lithium iron manganese phosphate positive electrode material synthesis process route, which can not only quickly prepare the lithium iron manganese phosphate precursor and greatly reduce the preparation time of the precursor, but also refine the particle size of the precursor and improve the cycle stability of the lithium iron manganese phosphate positive electrode material.

[0007] The technical solution of the present invention is: a method for rapidly preparing lithium manganese iron phosphate positive electrode material, comprising:

[0008] S1, forming a mixed solvent with a hydrophilic organic solvent and water in a volume ratio of (1-8):1, dissolving oxalic acid in the mixed solvent to obtain an organic / water blended oxalic acid solution, simultaneously and quickly pouring a divalent manganese salt solution and a divalent iron salt solution into the organic / water blended oxalic acid solution, stirring at room temperature for 0.5-4h, and obtaining a manganese iron oxalate precursor powder after separation, washing, and drying;

[0009] S2, wet-milling the ferromanganese oxalate precursor powder obtained in step S1 with a lithium source, a phosphorus source and a carbon source, and then taking it out and drying it for later use;

[0010] S3, calcining the mixed material dried in step S2, and grinding it after cooling to obtain lithium manganese iron phosphate positive electrode material.

[0011] In the above scheme, compared with the ordinary oxalic acid aqueous solution, a hydrophilic organic solvent and water are used to form a mixed solvent to dissolve oxalic acid, thereby accelerating the nucleation of the corresponding metal oxalate and limiting the growth size of the precursor. In addition, this scheme has the advantages of being fast and efficient.

[0012] Preferably, the particle size of the ferromanganese oxalate precursor powder is 0.5-4 μm. The present invention can achieve the reduction of the size of the precursor because the high volume proportion of organic solvent cannot dissolve the metal salt, the metal salt concentration in the mixed solution is relatively high, and the high proportion of organic solvent limits the size of the ferromanganese oxalate precursor.

[0013] Preferably, the hydrophilic organic solvent and water form a mixed solvent in a volume ratio of (3 to 5): 1. This ratio is very critical and can achieve the regulation of the size of the precursor. If the ratio of the hydrophilic organic solvent is too large, it will cause adverse effects such as difficulty in dissolving the metal salt, uneven reaction, and wide size distribution. If the ratio is too small, it will cause adverse effects such as failure to achieve rapid nucleation and limit the size of the precursor.

[0014] Preferably, in step S1, the hydrophilic organic solvent includes one or more of methanol, ethanol, propanol, ethylene glycol, glycerol, acetone, acetonitrile, etc.; the divalent manganese salt includes one or more of manganese sulfate, manganese acetate, and manganese chloride; the divalent iron salt includes one or more of ferrous sulfate, ferrous acetate, and ferrous chloride.

[0015] Preferably, in step S1, the concentration of oxalic acid in the organic / water blended oxalic acid solution is 0.4-1 mol / L; the molar concentration of manganese salt in the divalent manganese salt solution is a, and the molar concentration of iron salt in the divalent iron salt solution is b, a and b satisfy 0.1 mol / L≤(a+b)≤0.4 mol / L, a:b=(1.5-4):1. In this scheme, the concentration of the organic / water blended oxalic acid solution is greater than the concentration of (manganese salt + iron salt), the purpose of which is to ensure that the metal salt is fully reacted and precipitated, and to ensure the economy of the scheme; the concentration of manganese salt is 1.5-4 times that of iron salt, the purpose of which is to prepare lithium manganese iron phosphate material with a high manganese content.

[0016] Preferably, in step S1, the volume ratio of the organic / water blended oxalic acid solution, the divalent manganese salt solution and the divalent iron salt solution is (1-10): 1: 1. In this solution, the volume of the organic / water blended oxalic acid solution is the largest, while the volume of the metal salt solution is relatively small. The purpose is to prepare a high-concentration metal salt solution to minimize the oxidation of divalent metal salts, especially divalent iron salts, by oxygen dissolved in water; in addition, both metal salts cannot be dissolved in organic solvents, so only water is used as a solvent to prepare the metal salt solution, and the volume is relatively small.

[0017] Preferably, in step S2, the lithium source includes one or more of lithium carbonate and lithium hydroxide; the phosphate source includes one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate and lithium dihydrogen phosphate; and the carbon source is one or more of glucose, sucrose and starch.

[0018] Preferably, in step S2, the lithium source, phosphorus source and ferromanganese oxalate precursor are added at a molar ratio of lithium:phosphorus:(manganese+iron)=(1.0-1.2):(1.0-1.05):1, and the carbon source is added at 0.5-20wt% of the mixture formed by the ferromanganese oxalate precursor powder and the lithium source, phosphorus source and carbon source. Further, the carbon source is added at 10-15wt% of the mixture formed by the ferromanganese oxalate precursor powder and the lithium source, phosphorus source and carbon source.

[0019] Preferably, in step S2, the wet ball milling solvent is one or more of water, ethanol, methanol or acetone; and the ball milling time is 2-8 hours. The present invention only requires one ball milling because the precursor is small in size and the manganese iron has been distributed at the atomic level in the precursor, thus further saving the entire cathode material preparation time.

[0020] Preferably, in step S3, calcination is performed by a two-stage gradient heating method, specifically comprising:

[0021] The furnace temperature is raised from room temperature to 300-400°C, pre-burned for 2-6 hours, with a heating rate of 1-2°C / min; then the temperature is raised to 600-800°C, calcined for 5-10 hours, with a heating rate of 5-10°C / min.

[0022] Further, the furnace temperature is raised from room temperature to 350°C, pre-fired for 4 hours, with a heating rate of 1-2°C / min; then the temperature is raised to 700-750°C, calcined for 6-7 hours, with a heating rate of 5°C / min.

[0023] The present invention also provides a lithium iron manganese phosphate positive electrode material, which is prepared by any of the above methods for quickly preparing the lithium iron manganese phosphate positive electrode material.

[0024] The core of the present invention lies in: the organic / water blended oxalic acid solution has a high organic ratio, which promotes the rapid nucleation and confined growth of the precursor; the rapid, room temperature liquid phase method is used to prepare the precursor, avoiding metal ion oxidation during the production process, improving the purity of the sample, and realizing the atomic-level distribution of manganese and iron elements.

[0025] The beneficial effects of the present invention are:

[0026] 1. When preparing the precursor, a low-cost organic / water blended oxalic acid solution is used, and then the corresponding metal ion salt solution is added. The organic / water blended oxalic acid solution can achieve uniform and rapid nucleation and confined growth of the precursor, and realize the atomic-level distribution of metal elements in the precursor.

[0027] 2. Due to the rapid nucleation of the precursor, the present invention only needs to stir the reaction at room temperature for 0.5-4 hours. This method greatly shortens the reaction time, reduces energy consumption, and is more suitable for industrial production. At the same time, it effectively avoids the oxidation of metal ions in the preparation process and improves the purity of the product. On this basis, the preparation of high-quality lithium manganese iron phosphate positive electrode materials is achieved.

[0028] 3. In the present invention, due to the confined growth of the precursor in an organic / water mixed oxalic acid solution, the size of the prepared precursor is 0.5-4μm, which is much smaller than the existing size, and the manganese and iron in the precursor are distributed at the atomic level, thereby improving the cycle stability of the lithium manganese iron phosphate positive electrode material, and the capacity retention rate after 200 cycles at 0.5C is as high as 98.7%.

[0029] 4. The present invention only requires one-step ball milling process, which further saves the time for preparing the positive electrode material compared to the existing two-step ball milling.

[0030] 5. The specific surface area of ​​the lithium manganese iron phosphate positive electrode material prepared by the present invention is 23.45m 2 / g, the carbon content is 2.42%. The first cycle gram capacity is one of the key indicators for improving battery performance. The first cycle gram capacity of the present invention is as high as 162.3mAh / g@0.1C, indicating that it has good overall performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The preparation process flow chart of the present invention is

[0032] Figure 2 This is a scanning electron microscope image of the lithium manganese iron phosphate precursor obtained in Example 1

[0033] Figure 3 This is a scanning electron microscope image of the lithium manganese iron phosphate precursor obtained in Comparative Example 3.

[0034] Figure 4 Scanning electron microscope image of lithium manganese iron phosphate obtained in Example 1 DETAILED DESCRIPTION

[0035] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The drugs used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods in the art unless otherwise specified.

[0036] The embodiments of the present invention all prepare the lithium manganese iron phosphate positive electrode material according to the following method:

[0037] S1, forming a mixed solvent with a hydrophilic organic solvent and water in a volume ratio of (1-8):1, wherein the hydrophilic organic solvent is selected from one or more of methanol, ethanol, propanol, ethylene glycol, glycerol, acetone, acetonitrile, etc., and dissolving oxalic acid in the mixed solvent to obtain an organic / water mixed oxalic acid solution with a concentration of 0.4-1 mol / L;

[0038] The divalent manganese salt solution and the divalent iron salt solution are simultaneously and rapidly poured into the organic / water mixed oxalic acid solution, and the reaction is stirred at room temperature for 0.5-4h. The manganese salt is selected from one or more of manganese sulfate, manganese acetate, and manganese chloride, and the iron salt is selected from one or more of ferrous sulfate, ferrous acetate, and ferrous chloride. The molar concentration a of the divalent manganese salt solution and the molar concentration b of the iron salt in the divalent iron salt solution satisfy 0.1mol / L≤(a+b)≤0.4mol / L, a:b=(1.5-4):1, the volumes of the divalent manganese salt solution and the divalent iron salt solution are the same, and the volume ratio of the organic / water mixed oxalic acid solution, the divalent manganese salt solution, and the divalent iron salt solution is (1-10):1:1;

[0039] After the reaction is completed, ferromanganese oxalate precursor powder is obtained through suction filtration, washing and drying. The particle size of the ferromanganese oxalate precursor powder is 0.5-4 μm.

[0040] S2. The ferromanganese oxalate precursor powder obtained in step S1 is wet-milled with a lithium source, a phosphorus source and a carbon source for 2-8 hours, wherein the lithium source includes one or more of lithium carbonate and lithium hydroxide; the phosphate source includes one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate and lithium dihydrogen phosphate; the carbon source is one or more of glucose, sucrose and starch, and the dosage relationship is the molar ratio of the lithium source, phosphorus source and element content of the ferromanganese oxalate precursor Li:P:(Mn+Fe)=(1.0-1.2):(1.0-1.05):1, the mass percentage of carbon source / (precursor powder+lithium source+phosphorus source+carbon source)*100%=0.5-20%, and the ball milling solvent is one or more of water, ethanol, methanol or acetone. After the wet ball milling is completed, the mixture is taken out and dried for standby use.

[0041] S3. The mixed material dried in step S2 is calcined by a two-stage gradient heating method. The first stage is to increase the furnace temperature from room temperature to 300-400°C, pre-burn for 2-6 hours, and the heating rate is 1-2°C / min; the second stage is to increase the temperature to 600-800°C, calcine for 5-10 hours, and the heating rate is 5-10°C / min. After calcination, it is cooled in the furnace and then ground to obtain lithium manganese iron phosphate positive electrode material.

[0042] Example 1

[0043] This embodiment provides a method for quickly preparing a lithium manganese iron phosphate positive electrode material, the steps are as follows:

[0044] S1. A hydrophilic organic solvent (ethanol) and water are mixed in a volume ratio of 4:1 to form a mixed solvent, and oxalic acid is dissolved in the mixed solvent to obtain 1.0L of ethanol / water mixed oxalic acid solution (concentration is 0.8mol / L), and then a volume of 100ml, a concentration of a = 0.24mol / L manganese acetate solution and a volume of 100ml, a concentration of b = 0.16mol / L ferrous sulfate solution are quickly poured into the ethanol / water mixed oxalic acid solution, and the reaction is stirred at room temperature for 2h, and then a manganese iron oxalate precursor powder is obtained by suction filtration, washing, and drying;

[0045] S2, the ferromanganese oxalate precursor powder obtained in step S1 is wet-milled for 4 hours with a lithium source (lithium carbonate) and a phosphorus source (ammonium dihydrogen phosphate) according to the molar ratio of element content (Mn+Fe): Li:P=1:1.1:1.05, and the carbon source is glucose, and the amount of the carbon source is 10wt% of the mixture (i.e., precursor powder+lithium source+phosphorus source+carbon source), and the ball milling solvent used is ethanol, and then taken out and dried (i.e., vacuum dried) for standby use;

[0046] S3, the mixed material dried in step S2 is subjected to two-stage stepwise calcination, the first stage temperature rise program is from room temperature to 350°C, the temperature rise rate is 2°C / min, and the pre-calcination is 4h; the second stage temperature rise program is to heat up to 700°C, the temperature rise rate is 5°C / min, and the calcination is 7h. After cooling in the furnace, the mixture is ground to obtain lithium manganese iron phosphate powder.

[0047] The electron scanning electron microscope image of the lithium manganese iron phosphate precursor in Example 1 is as follows: Figure 2 As shown, from Figure 2 It can be seen that the size distribution of the manganese iron oxalate precursor is uniform (~2μm). The final lithium manganese iron phosphate powder is as follows Figure 4 As shown, from Figure 4 It can be seen that the primary particle size of the prepared lithium manganese iron phosphate material is ~200nm.

[0048] Example 2

[0049] This embodiment provides a method for quickly preparing a lithium manganese iron phosphate positive electrode material, the steps are as follows:

[0050] S1. A hydrophilic organic solvent (acetone) and water are mixed in a volume ratio of 3:1 to form a mixed solvent, and oxalic acid is dissolved in the mixed solvent to obtain 1.0L of acetone / water mixed oxalic acid solution (concentration is 0.8mol / L), and then a volume of 100ml, a concentration of a = 0.28mol / L manganese acetate solution and a volume of 100ml, a concentration of b = 0.12mol / L ferrous sulfate solution are quickly poured into the acetone / water mixed oxalic acid solution, stirred at room temperature for 2h, and then filtered, washed, and dried to obtain a manganese ferrooxalate precursor powder;

[0051] S2, the ferromanganese oxalate precursor powder obtained in step S1 is mixed with a lithium source (lithium carbonate) and a phosphorus source (ammonium dihydrogen phosphate) in a molar ratio of (Mn+Fe): Li: P=1:1.2:1.05, and the carbon source is glucose, and the amount of the carbon source is 15wt% of the mixture (i.e., precursor powder+lithium source+phosphorus source+carbon source), and wet ball milled for 4h, and the ball milling solvent used is acetone, and then taken out and dried (i.e., vacuum dried) for standby use;

[0052] S3, the mixed material dried in step S2 is subjected to two-stage stepwise calcination, the first stage temperature rise program is from room temperature to 350°C, the temperature rise rate is 2°C / min, and the pre-calcination is 4h; the second stage temperature rise program is to heat up to 700°C, the temperature rise rate is 5°C / min, and the calcination is 7h. After cooling in the furnace, the mixture is ground to obtain lithium manganese iron phosphate powder.

[0053] Example 3

[0054] This embodiment provides a method for quickly preparing a lithium manganese iron phosphate positive electrode material, the steps are as follows:

[0055] S1. A hydrophilic organic solvent (methanol) and water are mixed in a volume ratio of 5:1 to form a mixed solvent, and oxalic acid is dissolved in the mixed solvent to obtain 1.0L of methanol / water mixed oxalic acid solution (concentration is 0.8mol / L), and then a volume of 100ml, a concentration of a = 0.28mol / L manganese acetate solution and a volume of 100ml, a concentration of b = 0.12mol / L ferrous sulfate solution are quickly poured into the methanol / water mixed oxalic acid solution, stirred at room temperature for 2h, and then filtered, washed, and dried to obtain a manganese ferrooxalate precursor powder;

[0056] S2, the ferromanganese oxalate precursor powder obtained in step S1 is mixed with a lithium source (lithium carbonate) and a phosphorus source (ammonium dihydrogen phosphate) in a molar ratio of (Mn+Fe): Li: P=1:1.1:1.05, and the carbon source is glucose, and the amount of the carbon source is 10wt% of the mixture (i.e., precursor powder+lithium source+phosphorus source+carbon source), and wet ball milled for 4h, and the ball milling solvent used is ethanol, and then taken out and dried (i.e., vacuum dried) for standby use;

[0057] S3, the mixed material dried in step S2 is subjected to two-stage stepwise calcination, the first stage temperature rise program is from room temperature to 350°C, the temperature rise rate is 1°C / min, and the pre-calcination is 4h; the second stage temperature rise program is to heat up to 750°C, the temperature rise rate is 5°C / min, and the calcination is 6h. After cooling in the furnace, the mixture is ground to obtain lithium manganese iron phosphate powder.

[0058] Comparative Example 1

[0059] This comparative example provides a method for producing a lithium manganese iron phosphate positive electrode material, the steps of which are as follows:

[0060] (1) 1.0 L of ethanol / water mixed oxalic acid solution (oxalic acid concentration is 0.8 mol / L) is prepared by forming a mixed solvent of ethanol / water (volume ratio is 1:2), and then 100 ml of 0.24 mol / L manganese acetate solution and 100 ml of 0.16 mol / L ferrous sulfate solution are quickly poured into the solution, stirred at room temperature for 2 h, and then filtered, washed, and dried to obtain a precursor powder;

[0061] (2) the precursor powder obtained in step (1) is wet-milled for 4 h with lithium carbonate and ammonium dihydrogen phosphate in a molar ratio of (Mn+Fe):Li:P=1:1.1:1.05, with glucose as the carbon source and 10 wt % of the mixture (i.e., precursor powder+lithium source+phosphorus source+carbon source) as the ball milling solvent of ethanol, and then taken out and dried for later use;

[0062] (3) The mixed material dried in step (2) was calcined, and the first temperature program was from room temperature to 350°C, the heating rate was 1°C / min, and the pre-calcination was 4h; the second temperature program was further heated to 750°C, the heating rate was 5°C / min, and the calcination was 6h. After cooling in the furnace, the mixed material was ground to obtain a comparative lithium manganese iron phosphate powder.

[0063] Comparative Example 2

[0064] This comparative example provides a method for producing a lithium manganese iron phosphate positive electrode material, the steps of which are as follows:

[0065] (1) A 1.0 L methanol / water mixed oxalic acid solution (oxalic acid concentration is 0.8 mol / L) is prepared by forming a mixed solvent of methanol / water (volume ratio is 1:5), and then 100 ml of 0.24 mol / L manganese acetate solution and 100 ml of 0.16 mol / L ferrous sulfate solution are quickly poured into the solution, stirred at room temperature for 2 h, and then filtered, washed, and dried to obtain a precursor powder;

[0066] (2) The precursor powder obtained in step (1) is wet-milled for 4 h with lithium carbonate and ammonium dihydrogen phosphate in a molar ratio of 1:1.1:1.05, with glucose as the carbon source and 15 wt % of the mixture (i.e., precursor powder + lithium source + phosphorus source + carbon source) as the ball milling solvent of ethanol, and then taken out and dried for later use;

[0067] (3) The mixed material dried in step (2) was calcined, and the first temperature program was from room temperature to 350°C, the heating rate was 1°C / min, and the pre-calcination was 4h; the second temperature program was further heated to 750°C, the heating rate was 5°C / min, and the calcination was 6h. After cooling in the furnace, the mixed material was ground to obtain a comparative lithium manganese iron phosphate powder.

[0068] Comparative Example 3

[0069] (1) preparing 1.0 L of oxalic acid aqueous solution (oxalic acid concentration is 0.8 mol / L), then quickly pouring 100 ml of 0.24 mol / L manganese acetate solution and 100 ml of 0.16 mol / L ferrous sulfate solution into the solution, stirring at room temperature for 2 h, and then filtering, washing, and drying to obtain a precursor powder;

[0070] (2) The precursor powder obtained in step (1) is wet-milled for 4 h with lithium carbonate and ammonium dihydrogen phosphate in a molar ratio of 1:1.1:1.05, with glucose as the carbon source and 10 wt % of the mixture (i.e., precursor powder + lithium source + phosphorus source + carbon source) as the ball milling solvent of ethanol, and then taken out and dried for later use;

[0071] (3) The mixed material dried in step (2) was calcined, and the first temperature program was from room temperature to 350°C, the heating rate was 1°C / min, and the pre-calcination was 4h; the second temperature program was further heated to 750°C, the heating rate was 5°C / min, and the calcination was 6h. After cooling in the furnace, the mixed material was ground to obtain a comparative lithium manganese iron phosphate powder.

[0072] The precursor powder obtained in the preparation of Comparative Example 3 is as follows Figure 3 As shown, from Figure 3 It can be seen that the size of the precursor obtained using only water as solvent is larger than 10 μm.

[0073] Performance Testing

[0074] The above examples and comparative examples were subjected to precursor size test, specific surface area test, carbon content test, first cycle gram capacity test, first cycle coulomb efficiency test, and 0.5C cycle 200 cycle capacity retention rate test. The test results are shown in Table 1 below.

[0075] The carbon content is tested by a carbon-sulfur tester.

[0076] The first round of gram capacity testing was done by assembling a button half-cell, using metallic lithium for the negative electrode, and completing the test on a battery charge and discharge instrument.

[0077] The 0.5C cycle 200-week capacity retention rate test method is to assemble a button half-cell, use metallic lithium for the negative electrode, and complete the test on a battery charge and discharge instrument.

[0078] Table 1 Performance test data table

[0079]

[0080]

[0081] From the precursor size data in Table 1 above, it can be seen that adding organic solvent within a certain range directly affects the size of the product. The higher the proportion of organic solvent, the smaller the size of the obtained embodiment. Compared with the comparative example with less or no organic solvent added, the precursor size is larger; from the specific surface area data in Table 1 above, it can be seen that thanks to the control of the precursor size, the specific surface area of ​​the final product is larger, and the embodiment has the advantages of a shorter lithium ion migration path and more active sites exposed than the comparative example; from the carbon content data in Table 1 above, it can be seen that compared with the comparative example, the embodiment has a relatively high specific surface area and a relatively low carbon residue. The gram capacity of the embodiment is low, and the active component has the advantage of a higher proportion; from the first-cycle gram capacity data in Table 1 above, it can be seen that the embodiment has the advantage of a higher gram capacity, proving that the embodiment prepared by the present invention has a higher ability to store lithium ions and more fully exposed active sites than the comparative example; from the first-cycle coulomb efficiency data in Table 1 above, it can be seen that the lithium ion storage reversibility of the embodiment is better, and the embodiment prepared by the present invention has the advantage of less active lithium loss at the battery level compared with the comparative example; from the 0.5C capacity retention rate in Table 1 above, it can be seen that the embodiment prepared by the present invention has the advantage of more stable cycling compared with the comparative example.

[0082] The volume ratios of organic solvent to water in Comparative Examples 1-3 are not within the range specified in the present invention. It can be seen from the performance data that large-sized precursors will affect parameters such as specific surface area, gram capacity and cycle stability of the final product.

[0083] contrast Figure 2 and Figure 3 It can be seen that the embodiment prepared by the present invention has the advantages of smaller size and shorter ion migration path compared with the comparative example.

[0084] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for rapidly preparing lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: S1, forming a mixed solvent with a hydrophilic organic solvent and water in a volume ratio of (1-8):1, dissolving oxalic acid in the mixed solvent to obtain an organic / water blended oxalic acid solution, simultaneously and quickly pouring a divalent manganese salt solution and a divalent iron salt solution into the organic / water blended oxalic acid solution, stirring at room temperature for 0.5-4h, and obtaining a manganese iron oxalate precursor powder after separation, washing, and drying; S2, wet-milling the ferromanganese oxalate precursor powder obtained in step S1 with a lithium source, a phosphorus source and a carbon source, and then taking it out and drying it for later use; S3, calcining the mixed material dried in step S2, and grinding it after cooling to obtain lithium manganese iron phosphate positive electrode material.

2. The method for rapidly preparing lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step S1, the hydrophilic organic solvent includes one or more of methanol, ethanol, propanol, ethylene glycol, glycerol, acetone, acetonitrile, etc.; the divalent manganese salt includes one or more of manganese sulfate, manganese acetate, and manganese chloride; the divalent iron salt includes one or more of ferrous sulfate, ferrous acetate, and ferrous chloride.

3. The method for rapidly preparing lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step S1, the oxalic acid concentration in the organic / water mixed oxalic acid solution is 0.4-1 mol / L; the molar concentration of manganese salt in the divalent manganese salt solution is a, and the molar concentration of iron salt in the divalent iron salt solution is b, a and b satisfy 0.1 mol / L≤(a+b)≤0.4 mol / L, a:b=(1.5-4):

1.

4. The method for rapidly preparing lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step S1, the volume ratio of the organic / water blended oxalic acid solution, the divalent manganese salt solution and the divalent iron salt solution is (1-10): 1:

1.

5. The method for rapidly preparing lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step S2, the lithium source includes one or more of lithium carbonate and lithium hydroxide; the phosphate source includes one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate and lithium dihydrogen phosphate; and the carbon source is one or more of glucose, sucrose and starch.

6. The method for rapidly preparing lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step S2, the lithium source, phosphorus source and ferromanganese oxalate precursor are added in a molar ratio of lithium:phosphorus:(manganese+iron)=(1.0-1.2):(1.0-1.05):1, and the carbon source is added in an amount of 0.5-20wt% of the mixture formed by the ferromanganese oxalate precursor powder and the lithium source, phosphorus source and carbon source.

7. The method for rapidly preparing lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step S2, the ball milling solvent used in the wet ball milling is one or more of water, ethanol, methanol or acetone; and the ball milling time is 2-8 hours.

8. The method for rapidly preparing lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In step S3, calcination is performed by a two-stage gradient heating method, specifically comprising: The furnace temperature is raised from room temperature to 300-400°C, pre-burned for 2-6 hours, with a heating rate of 1-2°C / min; then the temperature is raised to 600-800°C, calcined for 5-10 hours, with a heating rate of 5-10°C / min.

9. The method for rapidly preparing lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The particle size of the ferromanganese oxalate precursor powder is 0.5-4 μm.

10. A lithium manganese iron phosphate positive electrode material, characterized in that: The material is prepared by any one of the methods for rapidly preparing lithium manganese iron phosphate positive electrode materials described in claims 1 to 9.

Citation Information

Patent Citations

  • Lithium manganese iron phosphate positive electrode material for realizing atomic-scale mixing of iron and manganese as well as preparation method and application of lithium manganese iron phosphate positive electrode material

    CN117334874A

Cited By

  • Production equipment and production method of lithium iron manganese phosphate positive electrode material precursor

    CN119500014A

  • Production equipment and method for producing lithium iron manganese phosphate positive electrode material precursor

    CN119500014B